Enhancing pre-service teachers' concept of Earth Science through an immersive, conceptual museum learning program (Reconceptualising Rocks). (October 2017) - Dawborn-Gundlach, L. Merryn; Pesina, Jenny; Rochette, Emily; Hubber, Peter; Gaff, Priscilla; Henry, Dermot; Gibson, Maria; Kelly, Leissa; Redman, Christine
Abstract: The collaboration between Museum Victoria and ReMSTEP partners: the University of Melbourne and Deakin University has enabled the development of the Reconceptualising Rocks project, designed to enhance the teaching of Earth Science for pre-service Science teachers. This study sought to determine how perceptions and understandings of Earth Science could be enhanced through immersion in the contextual learning in the Museum. Furthermore, the project aimed to explore how science ideas and practices can be translated for educational purposes. The findings revealed that participants found Earth Science interesting and were able to identify links to other Science areas. These findings have implications for the teaching of Earth Science across the curriculum. Highlights: Learning Experience Model for the contextual learning at the museum. Contemporary museum and scientific practices transfer into educational purposes. Implications for teaching Earth Science in secondary schools.